Examination of Pedagogical Content Knowledge of Pre-Service Primary School Teachers towards STEM - Kevser Sarı; Meltem Duran (Journal of Science Learning, 2023)
This study examines the pedagogical content knowledge of pre-service primary school teachers towards STEM. The research's study group consists of 202 pre-service primary school teachers studying at the faculty of education of two universities in the 2021-2022 academic year. The mixed method was used in the study. The survey model was used in the quantitative dimension of the study, and the case study was used in the qualitative dimension. The study's data were collected using the "STEM Pedagogical Content Knowledge Scale" and the "semi-structured interview form" developed by the researcher. A statistics program was used to analyze quantitative data, and content analysis was used to analyze qualitative data. According to the quantitative results of the study, the pedagogical content knowledge of pre-service primary school teachers towards STEM did not show the difference in terms of the variables of graduated high school, science proficiency, and desire to receive STEM education. In addition, differences were observed between the gender and technology sub-dimension, grade level and science and mathematics sub-dimension, having STEM knowledge and science sub-dimension, STEM competence and mathematics sub-dimension. According to the qualitative results of the study, it was determined that pre-service primary school teachers' perspectives toward STEM  education were positive. However, they considered themselves inadequate because they did not receive training.